WHY THE MUSLIM ORGANIZATIONS OF RUSSIA SPLIT - TULSKY, Mikhail (CENTRAL ASIA AND THE CAUCASUS, 2004)
In Soviet times the Muslims of the Russian Federation were supervised by two structures: the Spiritual Administration of the Muslims of the European Part of the U.S.S.R. and Siberia (SAMES) with headquarters in Ufa and the Spiritual Administration of the Muslims of the Northern Caucasus (SAMNC) based in Makhachkala. The former was headed by Mufti Talgat Tadjuddin elected on 19 June,1980; and the latter by Makhmud Gekkiev.